Foreign Direct Investments in Europe: Trends, Challenges, and Implications for Sustainable Economic Development - RĂDULESCU, Carmen Valentina; GÂF-DEAC, Ioan I.; ION, Laurențiu; BURLACU, Sorin (European Journal of Sustainable Development, 2025)
Foreign direct investment (FDI) is a category of investment that reflects the objective of establishing a lasting interest by an enterprise resident in one economy (direct investor) in an enterprise (direct investment enterprise) that is resident in an economy other than that of the direct investor. A lasting interest implies the existence of a long-term relationship between the direct investor and the direct investment enterprise and a significant degree of influence over the management of the enterprise. A lasting interest is considered to exist if the investor acquires at least 10% of the voting power of the direct investment enterprise. Keywords: economy, Europe, development, investments